2008
DOI: 10.1152/ajpcell.00616.2006
|View full text |Cite
|
Sign up to set email alerts
|

A hyperpolarization-activated, cyclic nucleotide-gated, (Ih-like) cationic current and HCN gene expression in renal inner medullary collecting duct cells

Abstract: A hyperpolarization-activated, cyclic nucleotide-gated, (Ihlike) cationic current and HCN gene expression in renal inner medullary collecting duct cells. Am J Physiol Cell Physiol 294: C893-C906, 2008. First published January 16, 2008 doi:10.1152/ajpcell.00616.2006The cation conductancein primary cultures of rat renal inner medullary collecting duct was studied using perforated-patch and conventional whole cell clamp techniques. Hyperpolarizations beyond Ϫ60 mV induced a time-dependent inward nonselective cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 66 publications
1
15
0
Order By: Relevance
“…Comparison with permeability and conductance ratios obtained from other preparations reveals that the values calculated here are within the same range [p Na /p K between 0.2 and 0.4 (for a review, see Pape, 1996); g Na /g K between 0.25 and 0.67 (e.g. Bolívar et al, 2008;Macri et al, 2002)]. …”
Section: Ion Selectivitysupporting
confidence: 74%
“…Comparison with permeability and conductance ratios obtained from other preparations reveals that the values calculated here are within the same range [p Na /p K between 0.2 and 0.4 (for a review, see Pape, 1996); g Na /g K between 0.25 and 0.67 (e.g. Bolívar et al, 2008;Macri et al, 2002)]. …”
Section: Ion Selectivitysupporting
confidence: 74%
“…14,15 RT-PCR analyses described in this report demonstrate that high levels of HCN3 and barely detectable levels of HCN2 are expressed in the proximal region of the upper urinary tract. Immunohistochemical studies showed that HCN2 expression is restricted to the renal tubules, 20 whereas we show that HCN3 expression is localized to the connective tissue layer underlying the smooth-muscle coat at the PKJ. Consistent with this HCN expression pattern, inhibition of HCN channel activity caused loss of spontaneous electrical activity at the PKJ, desynchronized the electrical propagation in the upper urinary tract, and caused abnormal peristalsis.…”
Section: Discussionmentioning
confidence: 48%
“…HCN2 expression has been localized to the inner medullary collecting ducts, 20 and to spatially localize HCN3 protein expression we performed chromogenic immunohistochemistry using 80-mm-thick urinary tract sections. HCN3 was highly expressed in the upper urinary tract at the PKJ and in the renal papilla (Figure 5d and e).…”
Section: Resultsmentioning
confidence: 99%
“…In the brain, they are shown to be related to learning, memory, and epilepsy [4,6,26]. Although there were previous studies showing the molecular expression of HCN isoform transcripts [27,33] or nicely demonstrating the functional expression of HCN currents [7] in non-excitable cells, to our best knowledge, there is no previous report on the function of HCN channels in non-excitable cells. In this study, it is clear that HCN blockers, cesium and ZD7288, decreased the proliferation and affected the cell cycle pattern of mESCs.…”
Section: Discussionmentioning
confidence: 94%